Evaluation of the relationship of signs and symptoms during the period of eruption of deciduous teeth - Rangel Bastos de Holanda Teixeira; Lorena de Alencar Gonçalves Ferreira do Amaral; Dayse Andrade Romão; Mariana Alencar Nemezio (Asociación Latinoamericana de Odontopediatría, 2019)
Introduction: Dental eruption is a physiological process, consisting of the migration of the tooth from its intraosseous position in jaw bones to buccal cavity. In infants it is associated with signs and symptoms such as irritability, gingival irritation, increased salivation, restless sleep, diarrhea, loss of appetite and fever. Objective: To assess mothers reports the occurrence of signs and symptoms during the eruption of deciduous teeth and whether the attitudes taken improve the child's condition. Material and Method: Data was collected from children (n = 50) aged 5 to 24 months. The signs and symptoms observed by the mothers during the eruption of deciduous teeth and attitudes taken by those responsible for the child were evaluated by means of a questionnaire. Results: The chi-square test (0.010) revealed an association of signs and symptoms with eruption of deciduous teeth. For the attitudes taken by the guardians regarding the symptomatology, the Chi-square test showed significant influence in the sample (0.009). Conclusion: It can be concluded that the mothers report the occurrence of signs and symptoms during the eruption of deciduous teeth and the attitudes taken by those responsible in relation to the symptomatology contribute to an improvement in the condition of the children.